The Racial College Completion Gap: Evidence From Texas. (2nd November 2017) - Flores, Stella M.; Park, Toby J.; Baker, Dominique J.
ABSTRACT: This analysis focuses on the college completion gap between underrepresented minority students and White students, or the Hispanic -White and Black -White racial college completion gaps, given the unprecedented demographic growth of these populations in the United States as well as the nation's public K -12 schools and postsecondary institutions. Using a variance decomposition method, we find that precollege characteristics (a combination of individual and high school context factors) contribute upward of 61% of the total variance for both Hispanic and Black students as compared with their White student counterparts. That is, more than half of the completion gap is explained by precollege characteristics. Postsecondary factors explained approximately 35% of the total variance. Additional analyses accounting for attending Hispanic-Serving Institution or an Historically Black College or University are also provided. The data suggest that college completion and accountability analyses should be approached from beyond a postsecondary perspective.